Pengaruh Kemampuan Pengelolaan Laboratorium Biologi UIN Sunan Gunung Djati Bandung - Raya Oktavia; Irawan Irawan; Tedi Priatna (Jurnal Dirosah Islamiyah, 2023)
The excellence of a biology education laboratory can be reflected in the quality and management profile it carries out. The purpose of this study was to determine the management system that is implemented in the Biology Education Integrated Laboratory at UIN Bandung. The research method uses a qualitative and descriptive method approach. The results showed that the implementation of laboratory management was classified as less than optimal and only part of it was running according to standard management rules. This is evidenced by the measurement results of planning indicators (planing) of 51.72% indicating positive or the "Good" category and as much as 41.37% are included in the "Less" category. While the other three management components consisting of organizing, actuating and controlling each indicator show results of 55.55% are in the "Good" category and 44.44% are considered "Less". The findings can be used as material for important studies in institutions to improve the laboratory management system gradually and continuously in order to obtain an ideal laboratory management function according to the proper regulations. Keywords: Management, Laboratory